Computer games in the EFL classroom - Schneider, Marie (Anchor Academic Publishing, 2014)
Fact is that commercial computer games play an extensive role in young people's lives, today. According to a recent study, 62 % of German teenagers play computer games at least once a week. This development led many researchers, school leaders and teachers to the question in how far games can be used to engage young people and support their learning inside the classroom. These considerations have been supported by various studies, showing that computer games can enhance various cognitive skills such as the ability of concentration, stamina, tactical aptness, anticipatory thinking, orientat.